2012
DOI: 10.1089/neu.2012.2498
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Mild Traumatic Brain Injury in a Mouse Model Produces Learning and Memory Deficits Accompanied by Histological Changes

Abstract: Concussion or mild traumatic brain injury (mTBI) represents the most common type of brain injury. However, in contrast with moderate or severe injury, there are currently few non-invasive experimental studies that investigate the cumulative effects of repetitive mTBI using rodent models. Here we describe and compare the behavioral and pathological consequences in a mouse model of single (s-mTBI) or repetitive injury (r-mTBI, five injuries given at 48 h intervals) administered by an electromagnetic controlled i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
267
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 255 publications
(301 citation statements)
references
References 64 publications
31
267
2
1
Order By: Relevance
“…From a neuropathological perspective, the 24‐month post injury data were consistent with our observations at earlier timepoints 13, 19. Mice exposed to repetitive injury displayed evidence of ongoing microgliosis localized to the CC.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…From a neuropathological perspective, the 24‐month post injury data were consistent with our observations at earlier timepoints 13, 19. Mice exposed to repetitive injury displayed evidence of ongoing microgliosis localized to the CC.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, our interinjury interval was 48 h, which is similar to our previous work,13, 19 a temporal window during which the mouse brain is known to be vulnerable to subsequent injuries21 in order to mimic human situations (combat or sports) in which additional injuries are sustained prior to full recovery from the previous injury. At the end of the procedure, each animal was removed from the stereotaxic table and allowed to recover on a heating pad and, upon becoming ambulatory, was returned to its home cage.…”
Section: Methodsmentioning
confidence: 85%
“…Several rodent models of rmCHI have been reported from two, three, five TBIs to 16 or 42 impacts at different intervals or frequencies. 23,24,[30][31][32][33][34][35][36][37] In the present study, we chose a mouse model of rmCHI with three impacts at an interval of 24 hours, as reported previously. 5,23,24 As shown in our results, our model displayed mild brain trauma with low NSS scores and the absence of intracranial hemorrhage and convulsions.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7] After human TBI, neuropathology studies have shown evidence of inflammation and progressive white matter degeneration following just a single moderate or severe TBI, 8 with imaging studies showing evidence of persistent neuroinflammation and reduced radial diffusivity and fractional anisotropy, even after mild injury. [9][10][11] Consistent with these findings, animal studies have shown persistent inflammation and axonal damage in the corpus callosum of mice exposed to repetitive mild TBI (r-mTBI) at chronic timepoints after injury, 12,13 with white matter disruption and an increase in radial diffusivity 60 days after repetitive mild TBI in rats.…”
Section: Introductionmentioning
confidence: 61%